Penilaian Kemiskinan Partisipatif pada Kawasan Transisi Perdesaan ke Perkotaan di Kabupaten Sragen - PRITA RAMADIANI; FADJAR HARI MARDIANSJAH (Journal of Regional and Rural Development Planning (Jurnal Perencanaan Pembangunan Wilayah dan Perdesaan), 2017)
Poverty in rural-urban transitional area has distinct characteristics from those in urban or rural poverty. This phenomenon can also be seen in Sragen Regency, peri-urban of Solo Raya. A descriptive analysis based on participatory poverty-assessment is conducted in this research in order to understand the poors in the transitional area. A set of questions was given to 100 poor households in urban agglomeration of Sragen. The main finding confirms that 29 households have better livelihood compared to 10 years ago, even though the improvements has not come as expected. Unequal distribution and different accessibility among community groups for urban facilities are identified as the common problems, as well as low standard of urban infrastructures provision in several neighborhoods which requires improvement. The increase of job opportunities is not followed significantly by occupational shift of the poors because of their limited competency and ability. Having this context, policies in such areas should not only related to urban facilities, infrastructures, as well as the living environment provision and improvement, but also needs some elements that focus on labor development, including improvement of competency and asset utilization for business development. These policies are needed in order to improve the quality of urban living environment without compromising the poor’s ability to compete in the rural-urban transitional situation.